Pengelolaan Program Pembinaan Kader Perempuan di Lingkungan Kohati (Korps HmI-Wati) Cabang Bandung - Iqhlima Yustpika Putri; Nan Rahminawati; Asep Dudi Suhardini (Bandung Conference Series: Islamic Education, 2024)
Abstract. The HmI-Wati Corps (Kohati) is part of a special body within HmI that focuses on fostering women related to issues related to women. Kohati was inaugurated during the congress in Solo on the fourth decree on September 17, 1966 with Kohati's basic guideline "Women are the pillars of the state" and has developed to this day. The issue of womenhood needs to be researched and studied, the rampant issue of women's dignity has greatly decreased in this world and in Indonesia. The problem that exists today, the lack of understanding of the role of women in the public and domestic realms, to answer this problem, there is the management of the cadre system at HmI wati as a forum for women's development which includes planning, organizing, moving, and supervising to improve quality. The purpose of this study is to find, identify and review the cadre system of the Bandung Branch of the HmI-Wati Corps. The research method used is qualitative analysis, which is expected to produce the output of HmI-Wati cadres who can have knowledge about the role of women in the public and domestic realms.The result of this study is that the HmI-Wati Corps Bandung Branch carries out cadres based on HmI guidelines, has an organized organizational structure, implements effective cadres so that HmI-Wati cadres have a good understanding of the role of women in the public and domestic realms, and are active in improving the quality of HmI-Wati cadres. Abstrak. Korps HmI-Wati (Kohati) merupakan bagian badan khusus di dalam HmI yang memiliki fokus dalam pembinaan perempuan terkait isu yang berkaitan dengan perempuan. Kohati di resmikan ketika kongres di solo pada penetapan keputusan yang keempat pada tanggal 17 September 1966 dengan Pedoman dasar Kohati “Wanita adalah tiang negara” dan berkembang sampai saat ini. Masalah tentang keperempuanan perlu diteliti dan dikaji, maraknya isu marwah perempuan sangat menurun di dunia ini dan di negara Indonesia. masalah yang ada saat ini, kurangnya pemahaman peran perempuan di ranah public dan domestic, untuk menjawab persoalan tersebut adanya pengelolaan sistem pengkaderan di HmI wati sebagai wadah pembinaan perempuan yang meliputi perencanaan, pengorganisasian, pergerakan, dan pengawasan untuk meningkatkan kualitas. Tujuan dari penelitian ini yaitu menemukan, mengidentifikasi dan mengkaji sistem pengkaderan Korps HmI-Wati Cabang Bandung. Metode penelitian yang digunakan adalah analisis kualitatif diharapkan menghasilkan output Kader HmI-Wati dapat memiliki pengetahuan tentang peran perempuan di ranah public dan domestic. Hasil penelitian ini adalah Korps HmI-Wati Cabang Bandung menjalankan pengkaderan berdasarkan pedoman HmI, memiliki struktur organisasi terorganisir, menerapkan pengkaderan efektif sehingga kader HmI-Wati memiliki pemahaman yang baik tentang peran perempuan di ranah public dan domestic, serta aktif untuk meningkatkan kualitas kader HmI-Wati.